Strategies against Nonsense: Oxadiazoles as Translational Readthrough-Inducing Drugs (TRIDs) - Campofelice, Ambra (Int J Mol Sci, 2019)
This review focuses on the use of oxadiazoles as translational readthrough-inducing drugs (TRIDs) to rescue the functional full-length protein expression in mendelian genetic diseases caused by nonsense mutations. These mutations in specific genes generate premature termination codons (PTCs) responsible for the translation of truncated proteins. After a brief introduction on nonsense mutations and their pathological effects, the features of various classes of TRIDs will be described discussing differences or similarities in their mechanisms of action. Strategies to correct the PTCs will be presented, particularly focusing on a new class of Ataluren-like oxadiazole derivatives in comparison to aminoglycosides. Additionally, recent results on the efficiency of new candidate TRIDs in restoring the production of the cystic fibrosis transmembrane regulator (CFTR) protein will be presented. Finally, a prospectus on complementary strategies to enhance the effect of TRIDs will be illustrated together with a conclusive paragraph about perspectives, opportunities, and caveats in developing small molecules as TRIDs.